Variable presentations of systemic lupus erythematosus based on presence or absence of antidouble stranded DNA antibodies: A case series - Maitra, Somnath; Sarkar, Swapan; Mukherjee, Biswaroop; Ghosh, Suprotim (Asian Journal of Medical Sciences, 2022)
Systemic lupus erythematosus (SLE) presents with diverse clinical features causing diagnostic challenges. Apart from the clinical features, autoantibodies are important for diagnosis along with certain laboratory parameters. Diagnosis is made with the European League against Rheumatism/American College of Rheumatology 2019 Criteria. The case series presented here signifies the correlation between anti ds DNA positivity and its association with poor prognosis and renal disease, whereas antidouble stranded DNA (anti-dsDNA) negativity may lead to lack of renal involvement and may be associated with polyserositis. The importance lies in the fact that these patients with anti-dsDNA negativity should be followed up for assessing conversion to positivity of anti-dsDNA, thus altering the prognosis and leading to renal involvement. Moreover, anti-SSA positive SLE patients must be followed up for possible development of sicca symptoms.